Investigation of effects of combustor wall thickness on the flame stabilization limits for micro combustors with wire mesh - Gheidan, Abdelgader Agilah Saleh (2017)
The scarcity of energy has led to the invention of alternative solutions to the conventional power generation system. Micro-power generation system is one of the potential sustainable solutions that provide better energy resource for small electronic devices as compared to conventional lithium-ion batteries. The difficulty to stabilize the flame in micro-combustors is the main obstacle faced by researchers, which is hugely caused from heat loss. Nevertheless, huge efforts towards attaining flame stabilization have been made within this few years back. In this research, the effect of combustor wall thickness on the flame stabilization limits of micro combustors with stainless steel wire mesh has been investigated. Numerical simulations were performed using a two-dimensional {2-D)and three dimensional (3-D) steady-state model. The wall thickness was varied from 0.3 mm to 1.2 mm. The governing equations were solved using ANSYS Release 16.2 with fluent capability. The blowout limits for each of wall thickness were determined. From the results, it is suggested that the flame stabilization limits for the combustors made of quartz tube has a direct relationship with the wall thickness flame stabilization limits. The results observed in the graph of combustor (quartz-quartz) (2-D) whenever increase thickness combustor from 0.3 mm to 1.2 mm this leads to more the flame stability that means the velocity blowout occurs at high value. But, in three dimension (quartz-quartz) (3-D) at velocity 0.47 m/s when increase thickness more than l mm it is not effective as results the better thickness of flame stability thickness 1 mm. Nevertheless, the strategy of improving flame stabilization limits by increasing the wall thickness has a limited range of effectiveness. The benefits of this project is to provide an alternative solution for saving more power energy consumption and to serve small scale of electronic device.